Educação cooperativista como recurso estratégico: o caso da Cooperativa Agropecuária São Gabriel do Oeste - COOASGO - Fernanda Mansilha da Silva Theodoro (2021)
Agricultural Cooperatives are inserted in an competitive scenario, having to act as an economically viable organization and, at the same time, as a social and democratic organization. These cooperatives generate jobs, distribute income and contribute – economically and socially – to regional development. In this way, Sousa et al. (2018) affirm that is relevant to study the management strategies of cooperatives, especially the importance given the practices of cooperative education. In this perspective, this study aimed to verify how cooperative education contributes to the strategic management of Agricultural Cooperative São Gabriel do Oeste - COOASGO. COOASGO invests in the training and professional qualification of its membership, promoting training, lectures and programs that aim at valuing its members and employees. The cooperative also has frequent participation in the programs, courses, seminars and lectures offered by Sescoop / MS. The literature review discussed the development of the Strategic Management field, addressed the theory of Resource-Based Vision and explained about Cooperative Education and Competitive Advantage in Agricultural Cooperatives. The development of the research occurred in two stages, in which the first stage of the methodological procedure, was a descriptive research of the Database, provided by OCB/MS. The Database, extracted from the Human Development Management System – GDH, contained data from agricultural cooperatives that training courses, programs and other activities developed by Sescoop/MS, in partnership with OCB/MS, in the period from 2017 to 2019. The second stage of the research, was an exploratory research, through a case study, in which interviews were conducted with three different stakeholders of the cooperative (associated, president and employees), in addition to the analysis of official documents of the cooperative. That said, the survey data indicated that agricultural cooperatives participated in various cooperative education practices, offered by Sescoop / MS, which has a broad portfolio of courses and programs. It was found that the cooperatives that most participated in the activities carried out by Sescoop / MS are cooperatives that have been operating in the market for more than 20 years, in addition, there is a greater attention by cooperatives for educational practices aimed at professional training and efficiency in the processes of education. cooperative, although cooperative education practices comprise both personal and professional development. The research also showed that when the cooperative includes cooperative education in its strategic planning, that is, it treats cooperative education as a strategic resource, it contributes to the achievement of better economic and social results. So, cooperative education practices, when focused on the two dimensions - social and professional - in a balanced way, have effects ranging from increased participation, professional qualification to quality in production and commitment, helping in the overall result of the cooperative. In addition, the contribution of cooperative education practices is not only in the realization of a course or program, but in a range of educational processes that occur in different ways, in a continuous manner. Still, the study found that it is not easy to work with cooperative education with the membership, it is hard, gradual work, which requires awareness and perseverance, since the economic and financial aspects are the biggest reasons to enter and remain in the cooperative.